Treatment Charges for Traumatic Brain Injury Among Older Adults at a Trauma Center. Issue 6 (November 2017) - Albrecht, Jennifer S.; Slejko, Julia F.; Stein, Deborah M.; Smith, Gordon S.
Abstract : Objective: To provide charge estimates of treatment for traumatic brain injury (TBI), including both hospital and physician charges, among adults 65 years and older treated at a trauma center. Methods: We identified older adults treated for TBI during 2008–2012 ( n = 1843) at Maryland's Primary Adult Resource Center and obtained hospital and physician charges separately. Analyses were stratified by sex and all charges were inflated to 2012 dollars. Total TBI charges were modeled as a function of covariates using a generalized linear model. Results: Women comprised 48% of the sample. The mean unadjusted total TBI hospitalization charge for adults 65 years and older was $36 075 (standard deviation, $63 073). Physician charges comprised 15% of total charges. Adjusted mean charges were lower in women than in men (adjusted difference, −$894; 95% confidence interval, −$277 to −$1512). Length of hospital and intensive care unit stay were associated with the highest charges. Conclusions: This study provides the first estimates of hospital and physician charges associated with hospitalization for TBI among older adults at a trauma center that will aid in resource allocation, triage decisions, and healthcare policy.